Linking Porter’s generic strategies to firm performance - Islami, Xhavit; Mustafa, Naim; Topuzovska Latkovikj, Marija (Springer Science and Business Media LLC, 2020)
AbstractIn this study, the significance of using Porter’s generic strategies in firms that operate in competitive environments is investigated. The aim is to indicate the effects of Porter’s generic strategies (low-cost strategy, differentiation strategy, and focus strategy) on firm performance. The questionnaires of the study have been prepared, the responses have been obtained, and the econometric model is constructed to measure these relationships. Findings stemmed by data that were taken from 113 firms that operate in the Republic of Kosovo. t test, Pearson’s correlation analysis, and multivariate regression analysis were used to provide testing of hypotheses. Econometric results suggest that pursuing differentiation strategy provides higher firm performance compared to two other Porter’s generic strategies (low-cost strategy or focus strategy) that have a positive impact as well.